Pengaruh Disiplin Kerja dan Karakteristik Individu Terhadap Kinerja Pegawai pada Badan Penanggulangan Bencana Daerah Kabupaten Karawang - Arista Ardiningrum; Suroso; Flora Patricia Anggela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of work discipline and individual characteristics on employee performance. The method used in this research is quantitative method. The population of this study consisted of 40 employees of the Karawang Regency Regional Disaster Management Agency. The sample of this study used a saturated sampling method, the entire population in this study was sampled. Data analysis was carried out using validity test, reliability test, normality test and hypothesis testing using t test (partial) and f test (simultaneous). The results of this study indicate that there is a partial influence between work discipline and employee performance with a value of 3,557. there is also a partial influence between individual characteristics and employee performance with a value of 2,341. The level of employee performance is jointly influenced by work discipline and individual characteristics. This can be seen from the F-count value of 49,707 which is greater than 2.85. Employee performance at the Regional Disaster Management Agency is influenced by individual characteristics and work discipline by 72.9%.